(untitled) (Medico Legal Update, 2019)
Deaths due to fall from height are the second leading cause of injury-related deaths. The fatalities of the injuries depend not only on the height of fall but also on the landing position and impact surface. Additionally, diversity of the injuries and the complexity of the patterns involved in these injuries, emphasizes the need for study in this area. A retrospective autopsy study of deaths due to fall from heights was carried out at the Department of Forensic Medicine, KIMS Hospital, Bangalore from January 2014 to December 2016. Among the total 1911 cases autopsied during the study period, 90 cases (4.07%) were deaths due to fall from height. Maximum number of cases was in the second decade of their lives (36.6%) and was followed by cases in third decade (21.1 %). male to female ratio was 6.5:1. About 41.1% of the cases were construction workers, followed by 15.5% students. Fatal height of fall was within 0-20 feet (48.8%) followed by 21- 40 feet (44.4%).Amongst the fatal fall, 63.3% of cases succumbed to injuries without treatment. It was observed that in 41.1% the impact was on hard surface followed by fall on tiles in 35.5%.Head injury was the leading cause of death in 51.1% of the cases. We concluded that fall from heights carry a significant morbidity and mortality and to decrease the incidence of these deaths, it is important to employ certain vital strategies. These include creating awareness amongst workers, increasing parental supervision of toddlers during their play at heights and psychological counseling for students.